The role of strategic vigilance in creating a competitive advantage in the target market of Telecom Algeria - Amina, Bin Ali (Journal of Economic, Administrative and Legal Sciences, 2017)
Business environment today is characterized by many change, therefore, the economic institutions must be vigilante to promote and create a competitive advantage within their target market. The vigilance strategy of the most important and the most recent steering systems that ensure business organizations survival and continuity in a rapidly changing environment and the complexity of what revered prone to a range of events leading to the development of the occurrence of the institution in crisis .This is what the present study is trying to confirm, through a questionnaire addressed to 30 workers in the Telecom Algeria in Béchar. The study concluded with the paying attention to the system of strategic vigilance in its three axes (commercial, competitive and technological), So that the organization can create a competitive advantage in the Algerian telecom market.
Keywords: strategic vigilance; competitive advantage; competitive range; business vigilance; competitive vigilance; technological vigilance